My sister's keeper - Picoult, Jodi (Prince Frederick, MD : Recorded Books, 2004)
All her life, 13-year old Anna has helped her sister fight leukemia. Anna has provided platelets, bone marrow, and even stem cells to ensure Kate's survival. But when their parents ask her to donate a kidney, Anna has had enough. She enlist the aid of a lawyer and announces her intention to sue for control of her own body.
Unabridged.
Compact discs.
Read by various narrators.
Keywords: Sisters; Teenage girls; Leukemia -- Patients; Organ donors; Sick children; Mothers and daughters; Domestic fiction